Transcriptional switch by activating transcription factor 2-derived peptide sensitizes melanoma cells to apoptosis and inhibits their tumorigenicity - Bhoumik, Anindita (National Academy of Sciences, 2004)
The notorious resistance of melanoma cells to drug treatment can be overcome by expression of a 50-aa peptide derived from activating transcription factor 2 (ATF2(50–100)). Here we demonstrate that ATF2(50–100) induced apoptosis by sequestering ATF2 to the cytoplasm, thereby inhibiting its transcriptional activities. Furthermore, ATF2(50–100) binds to c-Jun N-terminal kinase (JNK) and increases its activity. Mutation within ATF2(50–100) that impairs association with JNK and the inhibition of JNK or c-Jun expression by RNA interference (RNAi) reduces the degree of ATF2(50–100)-induced apoptosis. In contrast, TAM67, a dominant negative of the Jun family of transcription factors, or JunD RNAi attenuates sensitization of melanoma cells expressing ATF2(50–100) to apoptosis after treatment with anisomycin, which is used as a model drug. Mutations within the JNK binding region of ATF2(50–100) or expression of TAM67 or JunD RNAi attenuates inhibition of melanoma's tumorigenicity by ATF2(50–100). We conclude that inhibition of ATF2 in concert with increased JNK/Jun and JunD activities is central for the sensitization of melanoma cells to apoptosis and inhibition of their tumorigenicity.